Evaluation of French Bean (Phaseolus Vulgaris L.) Genotypes for Spring Season Planting in Mid Hills of Nepal - Subedi, Sujan; Gautam, Ishwori Prasad; Pradhan, Navin Gopal; Ghimire, Dipendra; Thapa, Sanjeeb (Nepalese Horticulture, 2022)
An experiment was conducted at National Horticulture Research Centre (NHRC), Khumaltar, Lalitpur, Nepal from March to July of 2019 and 2020 to identify suitable bean genotypes for spring season planting. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications having seven genotypes as treatments viz. Semi Light Long, Long Green Bean, Trishuli, Four Season, LB-37, Pahelo Gheusimi, and Khairo Gheusimi. Observations were recorded on morphological characters, yield, and yield contributing attributes. All genotypes under study showed significant differences among each other. Pahelo Gheusimi was found to be early maturing (81 days after sowing) whereas genotype Four Season had the longest harvesting duration (29 days). Similarly, pod length (20.52 cm) and pod weight (16.60 g) was recorded highest in Long Green Bean, while the highest pod diameter was recorded in Pahelo Gheusimi (12.59 mm). A significantly highest number of pods (92/plant) was observed in Four Season whereas the highest fresh pod yield (1030.3 g/plant) per plant was observed in Long Green Bean which was at par with Four Season (997.1 g/plant). The calculated yield per hectare was 2.5 times higher in Long Green Bean (28.66 t/ha) as compared to the national average in 2020. Both rust incidence and Yellow Bean Mosaic Virus susceptibility were found less in Long Green Bean and Four Season. Based on the two-year observations, Long Green Bean and Four Season were found to be promising for spring season planting.